EVALUATION OF THE MANAGEMENT EFFICIENCY OF THE SEISMIC MONITORING SYSTEM OF THE REPUBLIC OF ARMENIA USING ARTIFICIAL INTELLIGENCE METHODS (1991–2024) - Avetisyan, Andrey M.; Petrosyan, Karen P.; Harutyunyan, Gharib H.; Petrosyan, Goharik R.; Asatryan, Lusine K. (Proceedings on engineering sciences (Online), 2025)
Efficient management of seismic monitoring systems in seismically active zones is vital for building accurate databases, forecasting earthquakes, and ensuring earthquake-resistant infrastructure. The 1988 Spitak earthquake, which devastated Shirak and Lori, highlighted the need for strong seismic oversight. However, in 1991, Armenia’s government transferred the seismic monitoring system from the National Academy of Sciences to other state bodies, initially the Ministry of Emergency Situations and, more recently, the Ministry of Internal Affairs. These institutions, often headed by non-specialists, lacked the scientific expertise required to manage such a highly specialized field. As a result, seismic R&D has stagnated; access to crucial earthquake data remains limited for professionals. This research aims to evaluate the current management efficiency of Armenia’s seismic monitoring system using the ChatGPT model and address long-standing issues that persist despite the existence of numerous scientific publications on the subject. The findings could help inform future improvements in system oversight and access.